2020
DOI: 10.1159/000507398
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin Attenuates Cognitive Impairment in Streptozotocin-Induced Diabetic Rats: Underlying Mechanisms

Abstract: <b><i>Objective:</i></b> Prolonged diabetes mellitus causes impairments of cognition and attentional dysfunctions. Diosgenin belongs to a group of steroidal saponins with reported anti-diabetic and numerous protective properties. This research aimed to assess the effect of diosgenin on beneficially ameliorating learning and memory decline in a rat model of type 1 diabetes caused by streptozotocin (STZ) and to explore its modes of action including involvement in oxidative stress and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Our preliminary studies found that diosgenin and its derivatives had anti-inflammatory and anti-oxidative stress effects [16][17][18]. The effects and mechanisms of Drug D in AP are still unknown.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our preliminary studies found that diosgenin and its derivatives had anti-inflammatory and anti-oxidative stress effects [16][17][18]. The effects and mechanisms of Drug D in AP are still unknown.…”
Section: Discussionmentioning
confidence: 92%
“…Preliminary research in this laboratory found that Diosgenin (Figure 4ai) derivatives had anti-inflammatory and anti-oxidative stress effects [16][17][18]. Here, we tried to explore whether Drug D (one of Diosgenin derivatives) (Figure 4aii) acted as a GSDMD antagonist to protect AP.…”
Section: Drug D Targeting Gsdmd Protects Against L-arginine-induced N...mentioning
confidence: 99%
See 1 more Smart Citation
“…β-Sitosterol attenuates insulin resistance and high fat diet-induced detrimental changes via mediating IRS-1/AKT signaling for the management of T2DM [44]. Diosgenin ameliorates cognitive deficits in T2DM, owing to its amelioration of astrogliosis, inflammation, and oxidative stress [45]. Baicalein (10 −6 and 10 −5 mol/L) regulated glucose uptake, glycolysis, and gluconeogenesis of hepatocytes to treat T2DM [46].…”
Section: Discussionmentioning
confidence: 99%
“… 10 It has also been shown to treat successfully cardiovascular diseases such as Type 2 diabetes and neurodegenerative diseases. 11 Studies have shown that diosgenin can reduce cognitive impairment, 12 aortic vascular dysfunction, 13 and kidney damage in streptozotocin‐induced diabetic rats. 14 Diosgenin can alleviate testicular injury in streptozotocin diabetic rats by reducing apoptotic oxidative stress and inflammation, 15 and inhibits renal tubular epithelial fibrosis induced by high glucose (HG) through the epithelial–mesenchymal transition pathway.…”
Section: Introductionmentioning
confidence: 99%